Impact of Nitrogen Fertilization on Fruit Parameters of Four Cucurbita maxima Cultivars Grown in Poland - Karolina Kaźmińska; Aleksandra Korzeniewska; Renata Słomnicka; Agnieszka Gniazdowska; Grzegorz Bartoszewski (Agriculture)
Cucurbita maxima Duchesne is a cucurbit species cultivated worldwide due to its economic and nutritional value. C. maxima winter squash fruits are rich in carotenoids and dietary fiber, making them valuable raw materials for food products, especially for infants and children as ingredients in pomaces, mousses, and juices. Therefore, both the yield and quality of fruits are economically important traits. These traits depend mainly on factors such as cultivar and plant growing conditions, including nitrogen fertilization. This study aimed to evaluate the nitrate content in the fruit as well as the yield and fruit parameters of four winter squash cultivars, Bambino, Justynka F1, Otylia F1, and Mammoth Gold, under different nitrogen fertilization regimes of 100%, 50%, and 30% of the standard nitrogen dose. Two field experiments were conducted in 2021 and 2022. This study revealed that the nitrogen dose had a significant effect on the nitrate content in the fruit flesh. A lower nitrogen dose resulted in a lower nitrate content in the fruit. In addition, a decrease in fruit yield occurred when the plants were fertilized with 30% of the standard nitrogen dose, whereas when the plants were fertilized with 50% of the standard nitrogen dose, the fruit yield remained relatively unaffected. The cultivars used in the experiment differed significantly in terms of the traits studied. The lowest nitrate content in fruit flesh was found for Justynka F1; however, the most favorable fruit parameters were obtained for Otylia F1, for which, in both years of the experiment, high yield and fruit weight, dry matter content, and the thickest flesh among the tested cultivars were achieved. This study contributes to the understanding of fruit quality and cultivation techniques for winter squash under the climatic conditions of Poland.